Plan de marketing para el desarrollo turístico del sitio Río Pindo en la parroquia Uzhcurrumi. - Godoy Valencia, Lubin Eumelia; Sarmiento Castro, Alisson Nicole (Machala : Universidad Técnica de Machala, 2024)
This research work addresses the design of a marketing plan to enhance the tourism development of the Río Pindo site, located in the Uzhcurrumi parish, with the aim of improving its visibility and attractiveness in the tourism market. Through a mixed methodology, which combined surveys of visitors and residents, and interviews, the strengths and weaknesses of the site were identified, as well as the opportunities and threats it faces. The results reveal that, although Río Pindo has great natural potential for tourism, its development is limited by the lack of adequate promotion, insufficient infrastructure and poor training in digital technologies among local actors. The research concludes with the recommendation to implement a marketing plan that includes digital promotion strategies, improvements in tourism infrastructure and community training in the use of technological tools, in order to attract more visitors and ensure tourism development. sustainable that benefits the local community.
Este trabajo de investigación aborda el diseño de un plan de marketing para potenciar el desarrollo turístico del sitio Río Pindo, ubicado en la parroquia Uzhcurrumi, con el objetivo de mejorar su visibilidad y atractivo en el mercado turístico. A través de una metodología mixta, que combinó encuestas a visitantes y residentes, entrevistas, se identificaron las fortalezas y debilidades del sitio, así como las oportunidades y amenazas que enfrenta. Los resultados revelan que, aunque Río Pindo posee un gran potencial natural para el turismo, su desarrollo se ve limitado por la falta de promoción adecuada, insuficiencia en la infraestructura y una formación deficiente en tecnologías digitales entre los actores locales. La investigación concluye con la recomendación de implementar un plan de marketing que contemple estrategias de promoción digital, mejoras en la infraestructura turística y la capacitación de la comunidad en el uso de herramientas tecnológicas, con el fin de atraer a más visitantes y asegurar un desarrollo turístico sostenible que beneficie a la comunidad local.
Keywords: TURISMO; MARKETING; PROMOCION; DESARROLLO